Mental Health Problems and Self-Esteem among the Schoolchildren of Secondary School in Dharan - Poudel, Kamala; Dangol, Bhuwan Kumari; Shrestha, Roshana (Journal of Advanced Academic Research, 2019)
Introduction: Mental health and its related problems are growing concerns over the country. It is challenge to determine the epidemiology of childhood mental disorders. Early detection and effective intervention is necessary for holistic development of the futures citizens.Objectives: To assess the mental health problems and self-esteem of schoolchildren studying in urban Schools of Dharan Sub-metropolitan City.Materials and method: Cross-sectional descriptive research design was followed. The study population included schoolchildren studying in grade 9 and 10 in schools of Dharan (n = 450).  Simple random sampling technique was used to select the school and students. Mental health problems were assessed using self-administered Strength and Difficulties Questionnaire and self-esteem level was monitored using self-administered Rosenberg Self-esteem Scale. Data was analyzed by using descriptive and inferential statistics.Results: Majority (55.6%) of the students were male. Among the total students 12.9% had mental health problems. Gender difference was statistically significant as girls had higher (14.5%) mental health problem (p value = 0.027).Girls (15%) were statistically significant more likely to have emotional problems within domain of mental health problem than boys (p value = 0.003).) whereas boys had conduct problem. Self-esteem level was significantly negatively correlated with mental health problems (r = -0.256, p= 0.000). Conclusion: Mental health problem is high prevalent among school children. There was statistically significant negative correlation between mental health problems and self-esteem of the schoolchildren.